The Sherbrooke twins - Coulter, Catherine Ann. (New York : Jove Books, 2004)
The continuing saga of the Sherbrooke family. James and Jason Sherbrooke are the identical twin sons of the Earl of Sherbrooke, but they have very different personalities. When the Earl is shot at, his sons work together to find out who is trying to kill their father, and find love along the way.
Keywords: Historical fiction; Love stories; Regency fiction